Postmigration, Transculturality and the Transversal Politics of Art - Petersen, Anne Ring (Routledge Research in Art and Politics, 2024)
This is the first book to develop a postmigrant analytical perspective for the study of art, concentrating on how postmigration reopens the study of contemporary art and migration. The book introduces art historians and other scholars with a methodological interest in cultural analysis to the innovative concept of postmigration, offering a comprehensive introduction to the various meanings and uses of the term as well as translating it methodologically to an art historical context. The book analyses art projects from Denmark, Germany and Great Britain, which address some of the current challenges to European societies of immigration, and by drawing on theory from fields such as migration studies, transcultural studies and feminist, postcolonial and political theory, as well as re-engaging established concepts such as imagination, commemoration, belonging, identity, racialization, community, public space and participation. The book will be of interest to scholars working in art history, art and politics, migration studies, and transcultural studies.